Kesehatan Mental dalam perspektif Agama Islam - meydita dwi putri; Ahmad Saoki Munjaji; elisa harisah; fiqra muhamad nazib (Advances In Education Journal, 2024)
This study examines mental health from an Islamic perspective, focusing on how Islamic values, particularly those derived from the Qur'an and Hadith, offer holistic solutions to various mental health challenges. The research employs a systematic literature review method, analyzing 25 relevant articles. The findings reveal that mental health in Islam encompasses physical, mental, and spiritual dimensions, emphasizing a strong connection with Allah, worship practices, and values such as patience, gratitude, trust in Allah (tawakkul), and self-purification (tazkiyatun nafs). Islamic mental therapy models, such as remembrance (dhikr), night prayers, and repentance (taubah), positively influence individuals' mental and spiritual balance. However, challenges arise from the lack of public understanding of this approach and the stigma surrounding mental health disorders. Therefore, integrating Islamic values into modern mental health programs is a strategic solution to comprehensively enhance community mental well-being.